Indonesian Teachers' Attitudes towards Gifted Students with Low SES from Malay Background - Suhendri; Maryanah, Sri; Ediyanto; Norimune, Kawai (Indonesian Journal of Disability Studies, 2020)
Defined as a child who has superior capabilities, especially in the area of intelligence, many gifted children in Indonesia are ignored, especially those who have poverty issues in a rural area like Malay. This is disappointing as some theorists believe that Malay people are the indigenous people of Indonesia. The failure to recognize giftedness is believed due to the teachers' attitude towards gifted students with low SES (social-economic status). This study is a comprehensive and systemic literature review that analyses and synthesizes comprehensive works of literature from various journals obtained from Proquest central and Sage, books published in Indonesian and globally, government documentation, trusted websites, combined with the prescribed textbooks for studying giftedness at Flinders University. This study focuses on the Malay teachers' attitudes towards gifted students with low SES. The main finding of the study confirms that most Malay teachers deny the existence of gifted children, especially with low SES although some of them still try to identify these kinds of students based on teacher observation and the students' achievements.